The Influence of Compensation, Compensation and Leadership Style on the Productivity of MSME Partners in PT. Perkebunan Nusantara III Medan - Ruby April Motani Larosa; Valentino Arjun Surbakti; Leo Tarigan; Deni Faisal Mirza (Publikasi Indonesia, 2022)
Establishing a business requires good competence in the field, compensation is also needed as a reward for achieving work and also the leadership style must be good and can be used as an example for colleagues. This study aims to determine whether there is an influence of competence and leadership style on the productivity of MSME Partners at PT. Nusantara III Plantation, Medan. The object of this research is entrepreneurs who are members of the UMKM Partners at PT. Perkebunan Nusantara III Medan with a total sample of 96 respondents. The tool used to analyze the data is by using SPSS IBM 26. The data collection technique used is by distributing questionnaires to the respondents as much as the number of samples. Tests in this study using multiple linear regression analysis. From the results of data analysis, it can be concluded that competence, compensation and leadership style affect the productivity of MSME Partners at PT. Nusantara III Plantation, Medan. When viewed from the coefficient of determination test, the magnitude of the influence of competence, compensation and leadership style on MSME Partners at PT. Nusantara III Medan's plantations are 37%.